DNA Methyltransferases in Depression: An Update - Duan, Zhenghao; Lu, Jie (Frontiers in Psychiatry, 2020)
Depression is one of the most common psychiatric disorders affecting public health. Studies over the past years suggest that the methylation of some specific genes such as BDNF, SLC6A4, and NR3C1 plays an important role in the development of depression. Recently, epigenetic evidence suggests that the expression level of DNA methyltransferases differs in several brain areas including the prefrontal cortex, hippocampus, amygdala, and nucleus accumbens in depression patients and animal models, but the potential link between the expression level of DNA methylatransferase and the methylation of specific genes need further investigations to clarify the pathogenesis of depression.